Eye wash water flow direction study: an evaluation of the effectiveness of eye wash devices with opposite directional water flow - Fogt JS (Dove Medical Press, 2018)
Jennifer S Fogt, Lisa A Jones-Jordan, Joseph T Barr The Ohio State University College of Optometry, Columbus, OH, USA Introduction: New designs of eye wash stations have been developed in which the direction of water flow from the fountain has been reversed, with two water streams originating nasally in both eyes and flowing toward the temporal side of each eye. No study has been done to determine the ideal direction of water flow coming from the eye wash in relation to the eye. Materials and methods: Ophthalmic eye examinations were conducted before and after the use of two eye wash stations with opposite water flow directionality. Fluorescein was instilled in both eyes before using an eye wash to measure the effectiveness of the water flow. Subjects were surveyed upon their experiences using the eye washes. Conclusion: Ophthalmic examination found no significant difference in the efficacy of the eye washes with nasal-to-temporal water flow when compared to temporal-to-nasal water flow direction. Keywords: eye wash, ocular burn, cornea, water flow